Ação sobre a via nitrérgica, e sobre os canais de cloreto e de potássio ATP dependentes, como mecanismo adicional de ação da ioimbina no relaxamento do músculo liso do corpo cavernoso de humanos : estudo in vitro - Freitas, Fernando César Muniz (2007)
Introduction: About 52% of men aged between 40 and 70 years old suffer with erectile dysfunction (ED). Yohimbine (YOH), an α2-adrenergic blocker, has been used for ED treatment for several decades, and it still has its indications. However its mechanism of action still remains obscure. Most of the studies with YOH were made with corpus cavernosum and aorta of rats and rabbits, due to the difficulty of getting human tissue. The aim of this study is to define the non-cholinergic non-adrenergic mechanism of action of the YOH, evaluating the nitrergic pathway and the role of the ionic channels in the human cavernosum smooth muscle. Methods: The corpus cavernosum were removed from 13 male cadavers donors (18-53 years old), during surgery for removing of organs for transplant, following the national protocols for organs donation. The strips of human cavernosum muscle were vertically settled in parallel, in isometric register bath in KHS solution (pH 7,4, at 37ºC), constantly gassed with (O2-95% and CO2-5%). Curves dose-reply were performed with IOI (10-12 - 10-4 M) in strips of human corpus cavernosum beings pre-contracted with phenilefrine (10 µM) and with rich depolarizing solution in potassium (60 mM of K+), in association with nitrergic and ionic channels inhibitors (Na+, K+ and Cl-), for study of NANC ways. Results: The YOH provided an important relaxation for the strips of in vitro human corpus cavernosum under the dose of 10-4 M. After pre-contraction with phenilefrine (10 µM), the strips submitted to the YOH in this dose, got relaxed 95.8%, and when the pre-contraction was made with rich depolarizing K+ solution (60 mM of K+), Ca++ (2 mM), containing 10 µM guanethidine (chemical simpatolitic) e 10µM phentolamine (α-adrenergic blocker), the relaxation was of 69,5% (p<0,05). The YOH (10-4M), after pre-contraction with fenilefrina (10 µM), under the presence of 7-NI (10 µM) and of L-NAME (100 µM) (nitric oxide synthases inhibitors (nNOS and eNOS, respectively)), and of the ODQ (soluble guanylate cyclase enzyme inhibitor – 10 µM) provided relaxation of the human cavernosum muscle of 57,4%; 55.5%; 62.99%; respectively (p<0,05). In association with TTX (Tetrodotoxina - neuronal sodium channel inhibitor – 100 µM), TEA (tetraetilamonio - potassium channels voltage-dependents activated by calcium blocker – 100 µM), and with apamina + charybdotoxina (potassium channels activated by calcium blocker of low and high conductance - 0,1 µM + 1 µM), we got a relaxation of 56,4%; 100%; 100% respectively (p>0,05). With the glibenclamida (KATP and Cl- channels blocker – 10 µM), we got a 71,1% relaxation (p<0,05). Conclusion: The pharmacologic studies results suggest that the YOH relaxes the human corpus cavernosum by another mechanism different of his adrenergic blockade, possibly activating the nitrergic pathway, and through Cl- and KATP channels (NO - GUANILATO CICLASE - GMPc - chloride and KATP channels). The YOH doesn’t act through Na+ channels, and doesn’t act through potassium channels voltage-dependents activated by calcium, as well as it doesn’t act in the K+ channels activated by calcium of low and high conductance.